Implementation of Pancasila Values through a Sufism Approach to Build the Nationalism Attitude of Santri Jagad Alimussirry - Djoko Hartono; Ikrimatuz Zahro Setiyani (Journal Intellectual Sufism Research (JISR), 2022)
This study aims to describe the role of digital literacy as a solution to post truth phenomena in the era of information disclosure . This type of research is a qualitative research using the SLR ( Systematic Literature Review ) method. SLR is a literature review method that is collecting, identifying, mapping, critically evaluating research results on certain topics . The results of the study show that the post-truth phenomenon which is currently booming can be minimized by educating social network users about digital literacy. From these results, it can be seen that with the presence of digital literacy skills, individuals will be able to distinguish between correct and incorrect information. This is because digital literacy is also taught to think critically in responding, analyzing, and evaluating various information they receive so that a quality community group is formed that is free from hoax news . Thus, it can be concluded that digital literacy can be used as a solution in the post-truth phenomenon in the era of information disclosure.